A Speech Act Analysis of Persuasion and Evaluation in Marques Brownlee’s “M4 MacBook Air Review: Too Easy!” - Annisa Zahrani; Muhammad Hamzah; Fathya SWF Marpaung; Ariel Abenaya Simarmata (English Lecturers and Teachers Association (ELTA), 2026)
The growth of online review platforms has introduced ways where people share info and opinions together, though pragmatic strategies used in tech reviews aren't well studied yet. This study applies the Speech Act Theory by Searle (1969) with the purpose to examine illocutionary acts that are found in a YouTube video titled “M4 MacBook Air Review: Too Easy!” by Marques Brownlee (MKBHD). This study uses the descriptive qualitative approach to investigate how Marques Brownlee applies illocutionary acts with the purpose to educate, value, and persuade viewers in the context of technology review films. The corpus consists of 8 minutes and 16 seconds of spoken content, containing approximately 120 utterances extracted from the official YouTube subtitles. These subtitles were manually checked and validated for accuracy before analysis, and the data were examined through systematic coding, classification, and contextual interpretation. The study finds four kinds of illocutionary acts, such as assertive, expressive, directive, and commissive even though declarative activities rarely happened because of the informality of YouTube communication. Through directive and expressive acts, the video can engage and construct relationships with viewers, while at the same time, assertive acts affect in a dominant way, which underlines the main objective of MKBHD are distributing comprehensive and valuable information and also evaluating product performance as well. Finally, communicative actions typically indicate more intimate and sincere interactions. The results of the study show how online reviewers use language to build trust, maintain attention, and foster reader understanding, demonstrating that communicative actions help balance informative content with persuasive goals in technology reviews. Keywords : Illocutionary; Speech Act Theory; Pragmatics; Digital Communication